Food biotechnology, second edition - Shetty, Kalidas (Taylor & Francis Group, LLC, 2011)
Revised and updated to reflect the latest research and advances available, Food Biotechnology, Second Edition demonstrates the effect that biotechnology has on food production and processing. It is an authoritative and exhaustive compilation that discusses the bioconversion of raw food materials to processed products, the improvement of food quality, the importance of food safety, the design of ingredients for functional foods, and the biochemical advances made in traditional fermentation. It also provides an international perspective on the discipline as a whole.